A Ten Years Monitoring of Chlorofluorocarbons at the Antarctica: Results and Perspectives - MANGANI, FILIPPO; MAIONE, MICHELA; LATTANZI, LUCIANO; ARDUINI, JGOR (International Journal of Environmental Analytical Chemistry, 2001)
Chlorofluorocarbons are man-made long lasting atmospheric pollutants of great environmental concern, responsible for important global change phenomena. Recently, they were replaced by hydrogenated halocarbons that, even if less persistent, do not lack in environmental impact. Atmospheric concentrations of these compounds were measured in Antarctica by gas chromatography. The extremely low atmospheric mixing ratios of these compounds require a pre-concentration step of the air sample on suitable adsorbent in order to meet the sensitivity of the analytical method Results obtained analyzing air samples collected in Antarctica since 1988 for the determination of CFC-12 and CFC-11 are reported, together with data concerning the less abundant species.